2022
DOI: 10.3390/jfb13020071
|View full text |Cite
|
Sign up to set email alerts
|

Self-Crosslinkable Oxidized Alginate-Carboxymethyl Chitosan Hydrogels as an Injectable Cell Carrier for In Vitro Dental Enamel Regeneration

Abstract: Injectable hydrogels, as carriers, offer great potential to incorporate cells or growth factors for dental tissue regeneration. Notably, the development of injectable hydrogels with appropriate structures and properties has been a challenging task, leaving much to be desired in terms of cytocompatibility, antibacterial and self-healing properties, as well as the ability to support dental stem cell functions. This paper presents our study on the development of a novel self-cross-linkable hydrogel composed of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 81 publications
0
22
0
Order By: Relevance
“…Another chitosan-based hydrogel was developed by Mohabatpour and colleagues as a cell carrier for in vitro regeneration of tooth enamel [ 86 ]. The biomaterial complex of oxidized alginate and carboxymethyl chitosan was tested in 3 different compositions (4:1, 3:1 and 2:1 ratios).…”
Section: Bone Cartilage and Dental Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another chitosan-based hydrogel was developed by Mohabatpour and colleagues as a cell carrier for in vitro regeneration of tooth enamel [ 86 ]. The biomaterial complex of oxidized alginate and carboxymethyl chitosan was tested in 3 different compositions (4:1, 3:1 and 2:1 ratios).…”
Section: Bone Cartilage and Dental Tissuesmentioning
confidence: 99%
“…In all groups, the expression of alkaline phosphatase, a marker of enamel matrix mineralization, was found, which indicated the differentiation of HAT-7 cells in ameloblasts and possible restoration of enamel. In addition, hydrogels exhibited antibacterial properties against two cariogenic bacteria: Streptococcus mutans and Streptococcus sobrinus , which are involved in the formation of dental caries [ 86 ]. Taken together, the above findings support the idea of the multifunctional nature of chitosan.…”
Section: Bone Cartilage and Dental Tissuesmentioning
confidence: 99%
“…Today, studies have focused on using alginate-based biomaterials in dental TE-RM; alginate hydrogels with non-toxicity can be deployed for directing the differentiation of dental-derived stem cells [ 97 , 98 ]. In addition, injectable hydrogels can be deployed as carriers with excellent potential to incorporate cells or growth factors for dental tissue regeneration [ 99 ]. In one study, self-crosslinkable hydrogels were constructed from oxidized alginate and carboxymethyl chitosan as cell carriers for dental enamel regeneration (in vitro), showing suitable self-healing property.…”
Section: Te-rm Applicationsmentioning
confidence: 99%
“…These hydrogels also exhibited antibacterial activities against Streptococcus mutans and Streptococcus sobrinus . After in vitro enamel regeneration studies, it was revealed that the dental epithelial cell line, HAT-7, had high cell viability in the injected hydrogels [ 99 ]. In addition, an injectable, non-toxic, and biodegradable scaffold was developed using oxidized alginate microbeads, which encapsulated periodontal ligament and gingival MSCs [ 97 ].…”
Section: Te-rm Applicationsmentioning
confidence: 99%
“…Schiff base cross-linking reactions are reactions between molecules containing amine, alcohol, or hydrazide moieties and an aldehyde molecule [ 87 ]. The reactions involve a dynamic covalent amine bond formation via the cross-linking of amine groups and aldehyde groups and depend on the pH, temperature, and type of aldehydes/amines involved in the reaction [ 182 , 183 ]. Enzymes form covalent bonds between polymers, they are significantly sensitive and specific in chemical reactions [ 80 ].…”
Section: Mechanisms Of Gelationmentioning
confidence: 99%